Analisis Hubungan Komunikasi Interpersonal Dengan Motivasi Kerja Pegawai Dinas Pendapatan Dan Pengelolaan Keuangan Daerah Di Kabupaten Lebak - Hurriyah Agustini; Siti Hawaliah; Soleh Rosyad; Wildan . (E-Journal Studia Manajemen, 2013)
The purpose of this research was to examine empirically the effect between communications interpersonal on work motivation among the employees Regional Financial Revenue Management Official in Lebak Regional. The subjects of this research were 40 employees selected as samples by using proportion sampling technique taken from the overall population of 67employees. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the employees’ work motivation was positively affected by the communications interpersonal in Financial Revenue Management Official. The findings suggest that the variation of the work motivation of the employees might have been affected by communications interpersonal.